Peran Kepala Desa dalam Pengelolaan Dana Desa: Studi Kasus Desa Jepang Pakis Kabupaten Kudus - Wicaksono, Ferio Artahto (Hutanasyah : Jurnal Hukum Tata Negara, 2026)
The village is a community unit authorized to manage  governmental affairs and the interests of its citizens, led by a  Village Head. One of the main responsibilities of the Village  Head is managing village finances, including the village fund  (Dana Desa) sourced from the State Budget (APBN). To  ensure village funds are used effectively for development,  empowerment, and public services, transparent and accountable  management is required. This research uses a qualitative  approach    with an empirical juridical method through interviews, observation, documentation, and a review of laws, regulations, and literature. The purpose of this research is to  analyze the implementation of village fund governance by the Village Head and to provide recommendations for improving transparency and accountability. The results show that the management of village funds in Jepang Pakis Village, Jati District, Kudus Regency, is not yet fully in accordance with  provisions. A lack of openness is apparent in the planning,  implementation, and  budget accountability stages, which  insufficiently involve the community at large. This leads to  information gaps and low public participation. Strengthening governance is necessary  through  the  detailed  submission  of  budget reports, the provision of information via village public  media, and the implementation of regular community deliberations (musyawarah) to create transparent, accountable, and participatory village fund management.